Joint development as a value capture strategy in transportation finance - Zhao, Zhirong Jerry; Das, Kirti Vardhan; Larson, Kerstin (Journal of Transport and Land Use, 2012)
This article examines joint development as a value capture strategy for funding public transportation. We start from the concept of joint development, its rationale, a brief history, and the extent of its use. Joint development projects in Hong Kong, Taiwan, Tokyo, and Thailand are profiled, as well as domestic examples in Washington, DC, New York, NY, and Portland, OR, etc. Then we provide a framework to classify joint development models by ownerships (public or private) and by types of transaction (real property or development rights). Next, joint development is evaluated along four revenue criteria including efficiency, equity, sustainability and feasibility. Finally, we summarize the advantages and disadvantages of joint development as a transportation finance strategy, and provide recommendations for policy consideration or implementation.